The Use of Bill of Leading in the Transportation of Ships according to the Contract & Indonesian Law Perspective - Syarifur Ridho; Muhammad Arifin (JURNAL AKTA, 2024)
In transportation, the most important type of document is the bill of lading. It is called the most important document because, if there is a problem with the goods shipped or exported, the B/L has not been sent by the carrier, then the owner of the goods cannot make a claim to the carrier. Bill of lading or known as bill of lading is regulated in Article 506 of KUHD. This research uses a normative juridical research method with an analytical descriptive approach. Bill of Lading in sea transportation based on Indonesian law serves as proof of ownership of goods, and also as evidence of a transportation contract. Various documents that exist and are required in international trade transactions are grouped into the following categories: Preliminary documents, Main documents, Other important documents (additional documents). The Bill of Lading document is a document as one of the requirements for drawing up a Letter of Credit. The opening of a Letter of Credit is basically a contract and the agreed conditions regarding the withdrawal of a Letter of Credit must be fulfilled, such as the Bill of Lading document.